COMPETENCY-BASED ARABIC LANGUAGE LEARNING IN MADRASAH ALIYAH AT-THOHIRIYAH NGANTRU TULUNGAGUNG - Rudisunhaji, Muhamad Asngad; Dewi, Intan Sari; Nurcholis, Ahmad; Hidayatullah, Syaikhu Ihsan (Ijaz Arabi Journal of Arabic Learning, 2024)
Learning competencies are a reference for students' acting, behavioral, and thinking skills. The purpose of learning is to determine the type of material, strategies, methods, and media used in the learning process. Learning Arabic aims to foster language skills. On the other hand, there needs to be more theory and practice in its competency design and learning objectives. This study's data collection techniques use a phenomenological qualitative approach based on interviews, observations, and documentation. The findings indicate that its implementation has disadvantages, including the need for harmony between the elements of competence and the competencies applied. Second, there is a lack of achievement of learning objectives due to the formulation of learning objectives and the application of learning objectives that need to be followed by the theory of learning objectives. The design of competencies and the objectives of Arabic language learning will be achieved if the design and objectives of learning Arabic are based on the fundamental philosophical formulation of competency designs and the objectives of Arabic language learning.